2016
DOI: 10.1002/clc.22552
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Fitness With the Risk of Atrial Fibrillation: A Systematic Review and Meta‐Analysis

Abstract: Several studies have investigated the role of physical fitness in atrial fibrillation (AF), but the results remain controversial. We aimed to estimate the association between physical fitness and risk of AF. We comprehensively retrieved data from the Cochrane Library, PubMed, and Embase databases until February 29, 2016, for studies evaluating the association of physical fitness with the risk of AF. Data were abstracted from included studies, and effect estimates were pooled using a random-effects model. Six s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 42 publications
1
21
0
1
Order By: Relevance
“…As described previously, we strongly speculate that fitness might mitigate “the obesity paradox” in AF, as based on observations of heart failure and coronary heart disease . Our previous meta‐analysis showed that higher levels of physical fitness are associated with lower risks of recurrent AF, regardless of BMI. Additionally, maintaining or taking up physical activity resulting in improved fitness is associated with a reduced risk of AF and its outcomes.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As described previously, we strongly speculate that fitness might mitigate “the obesity paradox” in AF, as based on observations of heart failure and coronary heart disease . Our previous meta‐analysis showed that higher levels of physical fitness are associated with lower risks of recurrent AF, regardless of BMI. Additionally, maintaining or taking up physical activity resulting in improved fitness is associated with a reduced risk of AF and its outcomes.…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, regardless of BMI, high levels of fitness are associated with better health outcomes (eg, lower mortality and cardiovascular disease risk) . In fact, obesity is significantly associated with an increased risk of cardiovascular death only when combined with low fitness health levels, whereas it is not associated with an increased risk when combined with moderate to high fitness health levels . Currently, available data strongly support the hypothesis that high fitness appears to offset obesity with regard to the negative effects of cardiovascular health .…”
Section: Discussionmentioning
confidence: 96%
“…Physical activity is associated with small reductions in AF risk, even in overweight patients . Our previous meta‐analysis found that a higher level of physical fitness was associated with a lower risk of AF . Specifically, Pathak et al studied obese patients with symptomatic AF who were divided into 3 groups based on their baseline cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…65,66 Our previous metaanalysis found that a higher level of physical fitness was associated with a lower risk of AF. 67 Specifically, Pathak et al 68 studied obese patients with symptomatic AF who were divided into 3 groups based on their baseline cardiorespiratory fitness. After 4-year follow-up, the rate of AF recurrence was 88%, 65%, and 34% in the low-, adequate-, and high-fitness groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis and recent state-of-the-art review of AF indicated an inverse association between fitness and the risk of AF. 8,9 However, it is unclear whether higher fitness results in the greater benefit. Little is known about the point of fitness at which the benefits diminish or there is a decrease in the risk of AF.…”
Section: Mandeep R Mehra MDmentioning
confidence: 99%